New R2-CHA2DS2-VASc score predicts no-reflow phenomenon and long-term prognosis in patients with ST-segment elevation myocardial infarction after primary percutaneous coronary intervention - Zhang, Qinyao; Hu, Meirong; Ma, Shumei; Niu, Tiesheng (Frontiers in Cardiovascular Medicine, 2022)
Aims Evaluating the prognostic validity of new R2-CHA2DS2-VASc score for no-reflow phenomena and long-term prognosis in patients following primary percutaneous coronary intervention (PCI) with ST-elevation myocardial infarction (STEMI). Materials and methods From January 2017 to December 2018, a total of 401 patients with STEMI were continuously enrolled. According to the cut-off value, the patients were separated into two groups: R2-CHA2DS2-VASc < 3 group (n = 275) and R2-CHA2DS2-VASc ≥ 3 group (n = 126). Results With a sensitivity of 52.6% and a specificity of 73.1%, the optimal cut-off value for predicting no-reflow is R2-CHA2DS2-VASc ≥ 3. R2-CHA2DS2-VASc ≥ 3 as the ideal cut-off value for predicting major adverse cardiovascular events (MACE) with an area under the curve (AUC) of 0.781 [95% Confidence interval (CI): 0.738–0.801, P 0.001], a sensitivity of 50%, and a specificity of 91.1%. The incidence of MACE, death from all causes, and worsening heart failure was greater in the R2-CHA2DS2-VASc ≥ 3 group, although there was no significant difference in the incidence of repeated revascularisation procedures following PCI between the two groups. R2-CHA2DS2-VASc ≥ 3 was also an independent predictor of MACE (hazard ratio = 2.48, 95% confidence interval CI: 1.33–4.62, P = 0.04). Moreover, this score has a greater sensitivity (66.7%) and specificity (88.7%) for predicting the progression of heart failure. Conclusion R2-CHA2DS2-VASc ≥ 3 was independently associated with no-reflow phenomenon and poor clinical outcomes for patients in STEMI after primary PCI.